2011
DOI: 10.1111/j.1540-4560.2011.01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Going Beyond the Multicultural Experience—Creativity Link: The Mediating Role of Emotions

Abstract: This research examines the mediating role of emotions implicated in the multicultural experience-creativity link. We propose that when individuals are dealing with apparent cultural contradictions upon encountering two cultures simultaneously, mentally juxtaposing dissonant cultural stimuli could lower positive affect or increase negative affect, which could in turn induce a deeper level of cognitive processing of cultural discrepancies and inspire creativity. Two studies compared dual cultural exposure versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 33 publications
2
42
0
5
Order By: Relevance
“…As a result, the perceivers become sensitive to the cultural significance of the stimuli (e.g., the presence of a Starbucks Coffee Shop) in the environment. Torelli et al also showed that simultaneous activation of two cultures could increase defensive, exclusionary reactions when the perceiver experiences globalization as a threat to their heritage culture (see also Chen & Chiu, 2010; Cheng, Leung, & Wu, 2011).…”
Section: Cultural and Intercultural Implications Of Globalizationmentioning
confidence: 99%
“…As a result, the perceivers become sensitive to the cultural significance of the stimuli (e.g., the presence of a Starbucks Coffee Shop) in the environment. Torelli et al also showed that simultaneous activation of two cultures could increase defensive, exclusionary reactions when the perceiver experiences globalization as a threat to their heritage culture (see also Chen & Chiu, 2010; Cheng, Leung, & Wu, 2011).…”
Section: Cultural and Intercultural Implications Of Globalizationmentioning
confidence: 99%
“…The moderating role of global orientations in multicultural experiences can also be explored. For example, though exposure to the juxtaposition of cultural stimuli fosters cognitive creativity (Leung & Chiu, 2010;Leung et al, 2008), it can induce negative emotions and exclusionary reactions (Cheng, Leung, & Wu, 2011;Torelli et al, 2011). Note.…”
Section: Role Of Global Orientationsmentioning
confidence: 99%
“…First, our studies were the first to test the multicultural experience-creativity link on insight creativity. Whereas prior research predominantly tested the effect of multiculturalism on creativity measured by divergent thinking or idea generation tasks (e.g., unusual uses of a garbage bag, rewriting the Cinderella story for Turkish children; Cheng et al, 2011;, the current studies provided further evidence that multicultural experience can facilitate individuals' insight problem-solving ability, an important facet of creativity. Without replicating the main effect of different dual cultural primes (i.e., with or without self-relevant culture in the dual-cultural primes) on creativity performance (i.e., creative idea generation) reported in prior research (Cheng et al, 2011, study 2), the hypothesized interaction between perceived cultural distance and comparison mind-sets was replicated across Studies 1 and 2 with different insight problem-solving creativity tasks.…”
Section: Discussionmentioning
confidence: 88%